Volatile organic compounds produced by Bacillus velezensis L1 as a potential biocontrol agent against postharvest diseases of wolfberry - Ling, Lijun; Luo, Hong; Yang, Caiyun; Wang, Yuanyuan; Cheng, Wenting; Pang, Mingmei; Jiang, Kunling (Frontiers in Microbiology, 2022)
volatile organic compounds (VOCs) produced by antagonistic microorganisms have good biocontrol prospects against postharvest diseases. Infection caused by Alternaria iridiaustralis and 10 other significant fungal diseases can be successfully inhibited by VOCs produced by an identified and screened endophytic strain L1 (Bacillus velezensis). This study revealed the in vivo and in vitro biocontrol effects of VOCs released by B. velezensis L1 on A. iridiaustralis, a pathogenic fungus responsible for rot of wolfberry fruit. The inhibition rates of VOCs of B. velezensis L1 on the mycelial growth of A. iridiaustralis in vitro were 92.86% and 90.30%, respectively, when the initial inoculum concentration on the plate was 1 × 109 colony forming unit (CFU)/mL. Spore germination and sporulation were 66.89% and 87.96%, respectively. VOCs considerably decreased the wolfberry’s disease index and decay incidence in vivo. Scanning electron microscopy revealed that the the morphological and structural characteristics of A. iridiaustralis could be altered by VOCs. Ten VOCs were identified through headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS). Pure chemical tests revealed that 2.3-butanedione had the strongest antifungal effects, totally inhibiting A. iridiaustralis in wolfberry fruit at a 60 µL/L concentration. The theory underpinning the potential application of VOCs from B. velezensis is provided herein. This is also the first study to document the antifungal capabilities of the B. velezensis strain on postharvest wolfberry fruit.